PENDIDIKAN MODERASI BERAGAMA BAGI SISWA-SISWI SMA BHINNEKA TUNGGAL IKA JAKARTA - Urbanus Ura Weruin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
Along with the development of science, technology, and industrialization, the values of life change, includingreligious life. Spiritual and religious values are getting eroded. Life is increasingly opportunistic and materialistic.Hate speech, the spread of radical ideology, extreme religion, are easy to find on social media. As a pluralisticnation in terms of ethnicity, race, region and religion, Indonesia needs to develop an attitude of inclusiveness,tolerance, openness, solidarity and cooperation among various religious communities. Religious moderationeducation for every segment of society, especially educational institutions, is part of this ef ort. Because besidesaiming to develop intellectual abilities, education is also an ef ort to shape the moral character of students. It is inthis spirit that the PKM for Religious Moderation Education is being carried out with PKM partners for SMABhinneka Tunggal Ika Jakarta. Because the vision and mission of this school also emphasize religious values andsocial values such as openness, solidarity, tolerance and inclusiveness. This PKM activity which is carried outof line uses the 6D learning method (define, discover, dream, design, deliver, debrief) and jointly studies themeaning of religious moderation, the purpose and relevance of religious moderation education, moderation as theessence of religion, traditions religious moderation, and moderate attitudes in religion. The students are able toactively understand, formulate, and apply the values of religious moderation. This PKM succeeded in stimulatingstudents' moderate religious attitudes because students could formulate what is meant by religious moderation,moderate religious principles, and could cite examples of moderate attitudes in religion. The students are alsodetermined to apply these principles in their lives. ABSTRAK Seiring perkembangan ilmu pengetahuan, teknologi, dan industrialisasi, nilai-nilai kehidupan berubah, termasukkehidupan keagamaan. Nilai-nilai spiritual dan religius semakin tergerus. Hidup semakin oportunis danmaterialistik. Ujaran kebencian, penyebaran ideologi radikal, beragama secara ekstrim, mudah dijumpai di mediasosial. Sebagai bangsa yang majemuk dari segi suku, ras, daerah, dan agama, Indonesia perlu mengembangkan sikapinklusif, toleran, terbuka, solider, dan kerja sama antar berbagai umat beragama. Pendidikan moderasi beragamabagi setiap segmen masyarakat terutama lembaga pendidikan merupakan bagian dari upaya tersebut. Karena selainbertujuan untuk mengembangkan kemampuan intelektual, pendidikan juga merupakan upaya untuk membentukwatak moral peserta didik. Dalam semangat itulah PKM Pendidikan Moderasi Beragama ini dilakukan bersamamitra PKM SMA Bhinneka Tunggal Ika Jakarta. Karena visi dan misi sekolah ini pun menekankan nilai-nilaikeagamaan dan nilai-nilai sosial seperti terbuka, solider, toleran, dan inklusif. Kegiatan PKM yang dilakukan secaraluring ini menggunakan metode pembelajaran 6D (define, discover, dream, design, deliver, debrief) dan secarabersama-sama mempelajari pengertian moderasi beragama, tujuan dan relevansi pendidikan moderasi beragama,sikap moderat sebagai esensi beragama, tradisi-tradisi moderasi beragama, dan sikap-sikap moderat dalamberagama. Para siswa mampu secara aktif memahami, merumuskan, dan menerapkan nilai-nilai moderasi beragama.PKM ini berhasil menstimulasi sikap moderat beragama para siswa karena para siswa dapat merumuskan apa yangdimaksud dengan moderasi beragama, prinsip-prinsip beragama secara moderat, dan dapat menyebutkancontoh-contoh sikap moderat dalam beragama. Para siswa juga bertekad menerapkan prinsip-prinsip tersebut dalamkehidupan mereka.